Food habits and obesity: a study in adolescents - Bhattacharjee, Prasun; Mukhopadhyay, Sujaya; Joshi, Payas; Singh, Sahibjeet (International Journal of Contemporary Pediatrics, 2017)
Background: In India under nutrition was common but off late overweight and obesity, the diseases of over nutrition, has gained a foothold. Methods: This is a cross sectional study done in schools of Greater Noida city to see the food habits of adolescents and assess its impact on health in terms of being overweight and obesity. A total of 600 school children were included in the study. 4.0% (24) students were found to be obese while 12.8% (77) were overweight. Results: In this study, boys were more commonly overweight (44 out of 353, 7.3%) than girls (33 out of 247, 5.5%) while obesity prevalence was comparable in both the sexes (11 out of 353 i.e. 1.8% in boys and 13 out of 247 i.e. 2.1% in girls). Conclusions: Pearson’s correlation shows that BMI is significantly related to all the asked dietary habits at 0.05 levels and it is the frequency of having meals outside or skipping breakfast that is important.